Signature Verification And Forgery Detection Including Recognition Of Courtesy Amount In Cheques - Mohd Yusof, Mohd Hafizuddin (2005)
Bank cheque processing is an important task in financial institutions and for office automation. Owing tlo the immense difficulties involved in this task, little work has been reported until now. The present study makes a modest attempt towards automatic processing of a bank cheque along with the verification of the signatures extracted from the cheque.